2012
DOI: 10.1371/journal.pone.0044118
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Survey of Retracted Articles from the Scholarly Literature

Abstract: BackgroundThe number of retracted scholarly articles has risen precipitously in recent years. Past surveys of the retracted literature each limited their scope to articles in PubMed, though many retracted articles are not indexed in PubMed. To understand the scope and characteristics of retracted articles across the full spectrum of scholarly disciplines, we surveyed 42 of the largest bibliographic databases for major scholarly fields and publisher websites to identify retracted articles. This study examines v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
290
3
10

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(315 citation statements)
references
References 61 publications
12
290
3
10
Order By: Relevance
“…While the development of these databases indicates both an interest in and a desire to enhance the discoverability of retractions, databases such as these have been criticized as "impractical" in that they require additional searching on the part of researchers in addition to the initial identification of articles (Grieneisen & Zhang, 2012 (Crossref, 2017a). Several publishers represented in our study are members of Crossmark, including Elsevier, Springer, and Oxford University Press.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the development of these databases indicates both an interest in and a desire to enhance the discoverability of retractions, databases such as these have been criticized as "impractical" in that they require additional searching on the part of researchers in addition to the initial identification of articles (Grieneisen & Zhang, 2012 (Crossref, 2017a). Several publishers represented in our study are members of Crossmark, including Elsevier, Springer, and Oxford University Press.…”
Section: Discussionmentioning
confidence: 99%
“…Retracted publications are considered a rarity, making up only an estimated 0.02% of the biomedical literature (Grieneisen & Zhang, 2012). However, the rate of retractions has risen notably in recent years, with retraction notices in MEDLINE increasing 41% between 2014 and 2015 compared to the number of notices in 2013 and 2014 (U.S. National Li-brary of Medicine, 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although it is not easy to evaluate the amount of published scientific papers containing incorrect conclusions, the number of retractions may provide information on the problems associated with traditional peer-review. In 2012, Grieneisen and Zhang surveyed 42 of the largest bibliographic databases for major scholarly fields and publisher websites [44]. They found that the number of retractions has increased considerably after 2001.…”
Section: Open Peer-review: Transparent Research Evaluationmentioning
confidence: 99%
“…In recent years, the website RetractionWatch and other news media have helped investigate misconduct to assist editors in publishing an erratum or retracting a paper when authors were unwilling to cooperate with inquiries as in the case of the Wakefield study [8]. One would think that the harsh attention given to scientific misconduct by news media would serve to deter it, but it seems misconduct has gotten worse because "the number of articles retracted per year increased by a factor of 19.06 from 2001 to 2010" [9]. When adjusted for repeat offenders, the factor was closer to 11 [9].…”
mentioning
confidence: 99%
“…One would think that the harsh attention given to scientific misconduct by news media would serve to deter it, but it seems misconduct has gotten worse because "the number of articles retracted per year increased by a factor of 19.06 from 2001 to 2010" [9]. When adjusted for repeat offenders, the factor was closer to 11 [9].…”
mentioning
confidence: 99%